Clinical Retrospective Analysis of 340 Inpatients with Malignant Skin Tumors in Western Inner Mongolia - Min-Xin Jia; Dong-Xia Li; Yu-Lei Liu (Wolters Kluwer Health, 2021)
Abstract. Objective:. This study was performed to evaluate the clinical and epidemiological characteristics of inpatients with malignant skin tumors in western Inner Mongolia during the past 10 years. Methods:. We collected the clinical data of inpatients with histopathologically diagnosed malignant skin tumors admitted to the Affiliated Hospital of Inner Mongolia Medical University from June 2008 to December 2018. Morbidity was compared using the Chi-square test. Results:. In total, 340 inpatients with malignant skin tumors were evaluated, including 163 (47.94%) patients with basal cell carcinoma, 134 (39.41%) with squamous cell carcinoma, 5 (1.47%) with malignant melanoma, 21 (6.18%) with Bowen disease, and 6 (1.76%) with Paget's disease. Four (1.18%) patients had metastatic skin cancer and seven (2.06%) had other malignant skin tumors. The patients comprised 132 (38.8%) men and 208 (61.1%) women, and there were no statistically significant sex-related differences among the skin malignancies (x2 = 5.006, P > 0.05). Among the 340 patients, 314 (92.4%) were of Han nationality and 26 (7.6%) were of ethnic minorities. Statistically significant differences were found in the various types of malignant skin tumors between the Han and minority groups (x2 = 19.446, P < 0.05). Among the selected patients, 61.76% were farmers and herdsmen, and the sites mainly affected were the head, face, neck, trunk, limbs, and vulva. Conclusion:. The incidence of malignant skin tumors in western Inner Mongolia has substantially increased during the past decade, especially in the past 2 years. Therefore, we should increase the awareness of prevention and treatment of malignant skin tumors to achieve early diagnosis and treatment effects.